Emission mechanism in phosphorescent and fluorescent OLED utilizing energy transfer from exciplex to emitter. Issue 6 (22nd July 2016) - Takahashi, Tatsuyoshi; Seo, Satoshi; Nowatari, Hiromi; Hosoumi, Shunsuke; Ishisone, Takahiro; Watabe, Takeyoshi; Mitsumori, Satomi; Ohsawa, Nobuharu; Yamazaki, Shunpei
Abstract : This paper discusses the effectiveness of energy transfer from an exciplex to an emitter in both phosphorescent and fluorescent organic light‐emitting diodes. This energy transfer enhances the efficiency, lowers the drive voltage, and extends the lifetime. The increase in the quantum efficiency of a fluorescent organic light‐emitting diode using this mechanism is also analyzed. Abstract : This paper discusses the effectiveness of energy transfer from an exciplex to an emitter in both phosphorescent and fluorescent organic light‐emitting diodes. This energy transfer enhances the efficiency, lowers the drive voltage, and extends the lifetime. In particular, the quantum efficiency of the fluorescent organic light‐emitting diode was doubled based on this mechanism.